Penerapan Model Pembelajaran Think Pair Share Sebagai Upaya Mengembangkan Inisiatif Siswa Kelas XI IPA Dalam Pembelajaran: (Implementation of the Think Pair Share Learning Model as an Effort to Develop Initiatives of Class XI IPA Students in Biology Learning) - Situmeang, Rahul Simon; Tammu, Reisky (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
In the learning process, students are expected to show initiative as a form of their active involvement. Initiative is related to self starting, namely students are involved in learning actively based on their wishes, not just because of the teacher's stimulus and orders. Observations from one of the Tangerang private schools showed a lack of initiative by class XI IPA students in learning biology. This study aims to describe the application of the think pair share learning model to develop student initiatives in learning. The research method used is descriptive qualitative with an instrument in the form of a Field Experience Program portfolio 2 which consists of observation sheets, Teaching Implementation Plans, and teaching reflections. The results of the study show that the application of the think-pair-share learning model can develop student initiative in the learning process through the stages of thinking, discussing in pairs, and presenting or sharing the results of discussions in class (sharing). As for indicators of student initiative that developed after the implementation of think-pair-share, namely self-starting, proactive and persistent. The self-starting aspect of students is achieved through students' awareness to act independently in class, such as actively discussing and being involved in learning. Furthermore, the development of students' proactive aspects is shown through the real participation of students in the learning process such as initiatives to ask questions and respond to teachers. Student contributions in the process of solving problems will develop students' persistent aspects. Abstrak. Dalam proses pembelajaran, siswa diharapkan dapat menunjukkan inisiatif sebagai salah satu bentuk keterlibatan mereka secara aktif. Inisiatif berkaitan dengan self-starting yaitu siswa terlibat dalam pembelajaran secara aktif berdasarkan keinginan mereka bukan sekedar karena stimulus dan perintah guru. Hasil observasi si salah satu sekolah swasta Tangerang menunjukkan kurangnya inisiatif siswa kelas XI IPA dalam pembelajaran biologi. Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran think pair share untuk mengembangkan inisiatif siswa dalam pembelajaran. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan instrument berupa portfolio Program Pengalaman Lapangan 2 yang terdiri atas lembar obsenrvasi, Rencana Pelaksanaan Pengajaran, dan refleksi mengajar. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran think-pair-share dapat mengembangkan inisiatif siswa dalam proses pembelajaran melalui tahapan berpikir (thinking), berdiskusi secara berpasangan (pairing), dan mempresentasikan atau berbagai hasil diskusi dalam kelas (sharing). Adapun indikator inisiatif siswa yang berkembang setelah penerapan think-pair-share yaitu self-starting, proactive dan persistent. Aspek self-starting siswa tercapai melalui kesadaran siswa untuk bertindak mandiri dalam kelas, seperti aktif berdiskusi dan terlibat dalam pembelajaran. Selanjutnya, perkembangan aspek proactive siswa diperlihatkan melalui partisipasi nyata siswa dalam proses belajar seperti inisiatif untuk bertanya maupun merespons guru.Kontribusi siswa dalam proses menyelesaikan masalah akan mengembangkan aspek persistent siswa.